2018
DOI: 10.1021/acsaem.8b00215
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Native Defects with Ions and Its Role in Inducing Phase Transitions in p-Type S-Excess MoS2

Abstract: The effects of ion intercalation in transition metal chalcogenides like MoS2 has been well studied, although the nature of this interaction is not clearly known. In this Article, we show that defect-ion interaction is one of the key parameters that control many of the electrical, optical, structural, and electrocatalytic properties of MoS2. The results show for the first time that modulation of the concentration of intrinsic defects in MoS2 containing an excess of ‘S’ atoms in the lattice through Li+ insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Parts A and B of Figure illustrate the Nyquist plots of the measured impedance of OER process on pure Co 3 O 4 and V O –Co 3 O 4 in 1 M KOH from an open circuit potential (OCP) to 1.80 V. Combined with the corresponding Bode phase plots (Figure S10), these Nyquist plots were fitted with an equivalent circuit (Figure S11 and Tables S1–S6). The adsorption behavior of the reactants (OH • ) on the catalyst surface was described by R CT and CPE CT , where R CT and CPE CT represent the OH ions adsorption resistance and pseudocapacitance, respectively. , The changing trend of R CT and CPE CT could reveal the OH • evolution on the catalyst surface during OER. Similar studies have been reported for H • evolution in the HER process .…”
Section: Resultsmentioning
confidence: 99%
“…Parts A and B of Figure illustrate the Nyquist plots of the measured impedance of OER process on pure Co 3 O 4 and V O –Co 3 O 4 in 1 M KOH from an open circuit potential (OCP) to 1.80 V. Combined with the corresponding Bode phase plots (Figure S10), these Nyquist plots were fitted with an equivalent circuit (Figure S11 and Tables S1–S6). The adsorption behavior of the reactants (OH • ) on the catalyst surface was described by R CT and CPE CT , where R CT and CPE CT represent the OH ions adsorption resistance and pseudocapacitance, respectively. , The changing trend of R CT and CPE CT could reveal the OH • evolution on the catalyst surface during OER. Similar studies have been reported for H • evolution in the HER process .…”
Section: Resultsmentioning
confidence: 99%
“…For long‐term electrocatalytic applications, however, HER activity and stability of TMDs are paramount. In crystalline MoS 2 , basal plane activation, edge site exposure, and metal doping/incorporation/intercalation are the most employed strategies.…”
Section: Introductionmentioning
confidence: 99%
“…DFT investigations recommend that Li storage limits of graphene , can be improved by the presentation of impurities and defects. Surface imperfections can specifically affect alkali metal ion intercalation by changing the thermodynamics and increasing surface energy. , The idea of cooperation of intercalating particles with the intrinsic structural defects in MoS 2 was studied by DFT calculations, and progressive Li + addition into nonstoichiometric, S-excess MoS 2 prompts a semiconductor to metal electronic phase change . Experimental findings suggest that the electrode performance of graphene in LIBs can be upgraded by presenting intrinsic or extrinsic defects. , …”
Section: Introductionmentioning
confidence: 99%
“…29,30 The idea of cooperation of intercalating particles with the intrinsic structural defects in MoS 2 was studied by DFT calculations, and progressive Li + addition into nonstoichiometric, S-excess MoS 2 prompts a semiconductor to metal electronic phase change. 31 Experimental findings suggest that the electrode performance of graphene in LIBs can be upgraded by presenting intrinsic or extrinsic defects. 32,33 The defects in 2D materials change the electronic properties by creating active sites for substantial alkali−metal adsorption.…”
Section: Introductionmentioning
confidence: 99%